Development and Validation of Conditions for Extracting Flavonoids Content and Evaluation of Antioxidant and Cytoprotective Activities from Bougainvillea x buttiana Bracteas (var. Rose) - Rodolfo Abarca-Vargas; Alejandro Zamilpa; Vera L. Petricevich (MDPI AG, 2019)
In this study the effect of the ethanol concentration of Bougainvillea x buttiana extracts on the flavonoids content, and its antioxidant and cytoprotective activities in vitro were determined and compared. For the elucidation of the chemical constituents, the high-performance liquid chromatography method (HPLC) was used, and verification of the antioxidant activity was carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical method. The cytoprotective effects of extracts were determined by exposure to hydrogen peroxide. The HPLC analysis showed the presence of rutin, quercetin-3-glucoside and quercetin rhamnoside. Among the extracts investigated the best recuperation of the rutin content was observed in extracts with 80% ethanol (83 ± 5 mg/mL). The amounts of rutin present in all extracts contribute to the antioxidant capacity and the IC50 was 427.49 (0%), 275.41 (50%), 271.61 (80%), and 272.14 (100%) µg/mL. The lowest percentage of viability was found in the cultures exposed to 100% ethanol (92%). In cultures exposed to hydrogen peroxide the percentages of protection were 25%, 33%, 78%, and 65% for cultures treated for 72 h at 0%, 50%, 80%, and 100% ethanol, respectively. The ethanolic extract of B. x buttiana was confirmed to have high rutin content with potent antioxidant activity, low cytotoxic and strong cytoprotective effects.